TINJAUAN KEMBALI KEBERADAAN "KANAL" DI KOTA MAJAPAHIT - Sugeng Riyanto (Berkala Arkeologi, 2010)
Many researchers believe that the capital city of Majapahit was eguipped with intersected canals. This network of canals varies in its width, between 40 — 80m, and its depth was between 6 — 9 m. There are at least five canals strecthing in north - south direction and seven canal in east - west direction. The canals were cleariy described in many reports and publications as if their existence have been proved. In fact, the vestiges of this network of “canals” have never been examined thoroughly. Therefore, the lucid visual description of this “canal network” is actually untested yet. In oder to give more factual picture on the canals network, in 2007 the National Research Centre and Development of Archaeology conducted a field survey to trace back the actual condition of the canal. This article reports the result